The housing challenges of low-income older adults and the role of federal policy. Issue 3 (8th August 2018) - Stone, Robyn I.
ABSTRACT: Adequate housing is critical for low-income older adults, who face affordability and accessibility challenges that affect their quality of life, health, and ability to live independently in their communities. This article examines the federal policy role in meeting the housing and housing-related needs of the low-income elderly population, which is expected to grow as a proportion of all older adults over the next two decades. The availability of publicly subsidized units and vouchers is woefully inadequate to assist the current low-income elderly population in need of rental assistance. While access to affordable and accessible housing options has been a growing challenge for several decades, the Trump administration and Republican-majority Congress has an agenda and specific budgetary, administrative, and legislative proposals that would worsen the housing situation today and into the future. Population aging combined with a lack of investment in affordable senior housing and related programs over the last two decades requires a call to action for stakeholders in the public and private sectors to jointly develop a comprehensive national senior housing policy agenda and implementation strategy.